The Effect of Advertising and Personal Selling on Buying Decision with Brand Image as an Intervening Variable for Indofood Brand in Solo Raya - Dimas Raihan Putra Maulana; Wuryaningsih Dwi Lestari (Proceedings Series on Social Sciences & Humanities, 2024)
This research aimed to determine, through the use of the brand image as an intervening variable for the Indofood brand in Solo Raya, the direct or indirect effects of advertising and personal selling on purchasing decisions. Using purposive sampling combined with non-probability sampling approaches, 100 samples were employed in this investigation. With the use of SMART PLS 3.0 software, the Structural Equation Model Partial Least Square (SEM-PLS) was utilized as the analytical technique in this work. The analysis's findings demonstrate that: Advertising influences consumer behavior in a positive and significant way; personal selling influences consumer behavior in a positive and significant way; advertising influences consumer behavior in a positive and significant way; personal selling influences consumer behavior in a positive and significant way; and brand image influences consumer behavior in a positive and significant way. Additionally, brand image can mediate the relationship between advertising and consumer behavior through positive and significant outcomes. The Indofood brand has effectively employed advertising and personal selling as marketing methods to boost its sales and reputation.